Proposta da utilização de uma fibra de núcleo oco anti-ressonante para detecção simultânea de metano, monóxido de carbono e monóxido de nitrogênio - Silva, Artur de Araujo (2022)
Hollow-Core Anti-Resonant Optical Fibers (AR-HCF) is a novel hollow-core fiber with a low refractive index in the core and a high refractive index in the cladding. Unlike conventional solid-core optical fibers, where light confinement occurs by total internal reflection, in hollow-core fibers, this confinement can be explained by photonic bandgap mechanisms and by the theory of leaky modes. This work describes the simulations of AR-HCF using the finite element method (FEM), aiming its application in optical sensing. We performed numerical simulations using COMSOL Multiphysics software to study the propagation characteristics of AR-HCF. Also, we made simulation-related analyses, such as boundary conditions, size of mesh elements suitable to be used, and methods to reduce computational effort. Furthermore, this work demonstrates the potential application of AR-HCF as efficient sensors for the simultaneous detection of three gases: methane (CH4), carbon monoxide (CO), and nitrogen monoxide (NO). We investigated two fibers, one made of silicon oxide (SiO2) and indium(III) fluoride (InF3), to demonstrate the impact of the fiber material on performance over a wide wavelength range. We also considered in simulations the insertion of small holes perpendicular to the fiber length to enable the gas entry in the fiber's hollow core. The simulation results show that the designed fibers present low losses in the wavelengths of the absorption lines of the three gases. The highest attenuation value obtained in the simulations was 5.76dB/m for the SiO2 fiber and 0.06dB/m for the InF3 fiber, for λ = 5262.95 nm. Also, a linear behavior of the attenuation as a function of the gas concentration for the three gases of interest in the two designed fibers was obtained in the simulations. The sensitivity obtained by the sensor using an InF3 fiber with a length of 10 meters was 3.8x10^-2 (mV/ppm), 31x10^-2 (mV/ppm) and 11x10^-2 (mV/ppm) for the gases CH4, CO and NO, respectively. For the sensor using a SiO2 fiber with a length of 5 meters, the sensitivity estimated in this work was 1.9x10^-2 (mV/ppm), 15x10^-2 (mV/ppm) and 5.5x10^-2 (mV/ppm) for the gases CH4, CO and NO, respectively. In terms of the detection limits, the fiber made of InF3 material is capable of detecting concentrations of 13.2 to 86271 (ppm) of CH4, 1.6 to 10473 (ppm) of CO and 4.5 to 29340 (ppm) NO. The limits of detection for the fiber constituted of SiO2 were 26.5 to 163990 (ppm) of CH4, 3.2 to 20175 (ppm) of CO and 9.1 to 33034 (ppm) of NO.